Investigation of mechanical properties of aluminium-steel welding using different welding technique and processes - Mohd Sani, Idris (2013)
This report is presents about the investigation towards mechanical properties property of dissimilar welding by using different welding technique and processes. The objective of this research is investigate the weld joint quality of aluminium AA6061 and galvanized iron with different types of joining those are butt and lap joint and with different of welding processes, namely Metal Inert Gas (MIG) and Tungsten Inert Gas (TIG). The experiments carried out along this research such as non-destructive test (NDT), Vickers hardness test, tensile test and microstructure optical analysis. Based on the result of experiment, there are a few defects on weld appearances such as porosity, crack, and incomplete penetration. Butt joint of TIG welding (TBAG) shows a better weld appearance compared to other groups. Microstructure analysis showed that joint of TBAG has thinner brittle intermetallic compound layer (IMC) than the other group which shows thicker IMC, indicating a weaker joint. Based on the Vickers hardness analysis, the TIG welding shows higher hardness value than the MIG welding with average hardness value of 114 HV and 82 HV respectively , while tensile strength analysis showed that the butt joint samples has greater strength than the lap joint counterpart. TBAG has the highest tensile strength compared to the others group with value of 107 MPa while MLAG has the lowest strength with the value of 42 MPa. It can be concluded that TBAG is the best joint since TIG and butt joint showed the best value based on the analysis that had been carried out.